Efek Menejemen Nutrisi pada Status Nutrisi untuk Pasien Karsinoma Nasofaring Stadium Lanjut dalam Menjalani Kemoradiasi : Literatur Review - Nurnisaa Primadiah (Maternal & Neonatal Health Journal, 2023)
Malnutrition is an important clinical factor in the development and treatment of cancer. It results from a state when food intake fails to provide energy requirements. Malnutrition is very common in NPC patients because the original tumor site can significantly reduce food intake. International guidelines suggest intensive nutritional counseling (NC) and supplemental oral nutrition as nutritional interventions for head and neck cancer patients with CRT. It was also suggested that if cancer affects eating or swallowing, enteral nutrition (EN) should be given via a feeding tube. The purpose of this study was to investigate the effect of nutritional management in advanced NPC patients with CRT to evaluate nutritional status, and nutritional index and to observe nutritional status (weight, BMI, hemoglobin, albumin, prealbumin, and lymphocytes, and Quality of life (QOL). The method used is the literature review method with a systematic approach by tracing the results of experimental research in English. The articles used are focused on original empirical research articles or research articles that contain results from actual observations or experiments. The results obtained after a review of 3 articles that match the criteria Inclusion was that two studies gave results if nutritional interventions affected NPC patients after undergoing chemoradiation therapy, while one article stated that nutritional interventions did not affect NPC patients.